NMR relaxation time measurements of solvent effects in an organocatalysed asymmetric aldol reaction over silica SBA-15 supported proline. Issue 2 (17th January 2022) - Di Carmine, Graziano; Forster, Luke; Wang, Simeng; Parlett, Christopher; Carlone, Armando; D'Agostino, Carmine
Abstract : The behaviour of solvents in solid-supported proline organocatalysts is explored using NMR relaxation measurements coupled with reaction screening. Solvents with a lower affinity for the solid surface lead to a higher reactivity. Abstract : Immobilisation of organocatalysts onto solid supports represents a very promising solution to tackle their low productivity by enabling their reuse. Herein, the use of NMR relaxation measurements, coupled with reaction screening, was used to investigate the effect of solvent interactions with the immobilised catalyst matrix on reactivity in an asymmetric organocatalysed aldol reaction. Important insights for the further development of such complex, yet promising catalytic systems are provided.